HOW TAX AVOIDANCE, TAX RISK, AND FINANCIAL DECISIONS SHAPE FIRM VALUE IN INDONESIA UNDER SALES GROWTH MODERATION - Anggraeny, Dian; Solikhah, Badingatus (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2026)
The valuation impact of corporate tax behavior remains inconclusive in prior research, particularly in emerging markets, where institutional quality, transparency, and investor sophistication differ from developed economies. This research investigates the impact of tax avoidance, tax risk, capital structure, and dividend policy on firm value, while also exploring how sales growth may moderate these associations. Using panel data on non-financial companies listed in Indonesia from 2020 to 2024, the initial dataset covered 4,250 firm-year observations (850 firms over five years). After applying data availability and screening criteria, the final sample consisted of 2,471 firm-year observations. The study employs a fixed effects regression model to control for firm-specific heterogeneity and tests eight hypotheses. The findings show that tax avoidance and tax risk do not significantly affect firm value, while capital structure increases firm value, and dividend policy shows a negative effect. Sales growth strengthens the negative effect of tax avoidance and reinforces the positive effects of capital structure and dividend policy. Overall, financing and payout policies appear more influential in firm valuation than tax behavior, while growth conditions provide an important contextual influence in emerging markets.